Capillary seal capacity of faults under hydrodynamic conditions. Issue 3 (25th January 2016) - Underschultz, J.; Strand, J.
Abstract: Many fault bound traps are underfilled despite the top seal capacity being secure. The hydrocarbon sealing performance of faults themselves can be compromised either by mechanical or capillary process. Capillary process can be important either due to juxtaposition or to fine‐grained clay or cataclastic material within the fault zone itself. There is debate about how important each of these mechanisms is over geological timescales of hydrocarbon trapping. Recent work has provided insights into fine‐tuning capillary‐related fault seal calibration methodologies. Over the last 15 years, vigorous scientific debate with multiple published laboratory experiments and modelling studies has led some researchers and industry technologists to theorise that for water‐wet conventional hydrocarbon reservoirs, the relative water permeability in the reservoir (towards the top of the hydrocarbon column) may become very small, but in practice never reach zero. While not advocating for either side in this debate, the importance of accounting for hydrodynamic conditions regardless of the capillary sealing mechanism is demonstrated. Additionally, it is noted that nonzero relative water permeability has implications on how a seal's capillary threshold pressure for the nonwetting hydrocarbon phase is estimated from field data. In the particular case where there are pressure differences between unproduced hydrocarbon reservoirs on either side of a fault, then the hydrocarbon saturation must be discontinuous across the fault. For hydrocarbon leakage to occur across the entire thickness of the fault zone, the hydrocarbon pressure must exceed the threshold pressure on the side of the fault zone with the highest formation water hydraulic head. This approach to estimating across‐fault pressure difference will result in an improved calibration data set used for predrill estimation of capillary fault seal capacity.